KONTRIBUSI PENDIDIKAN ISLAM SYAIKH ALI HASAN AHMAD AD-DARY - Abidin, Zainal (Idrak: Journal of Islamic Education, 2018)
This paper describe the contribution of Syaikh Ali Hasan Ahmad Ad-Dary (scholars of hadis) on Islamic Education in North Sumatra. This research is the study of figures using library research. Islamic education activities in North Sumatra were initially held in the residences of preachers/ ulama and in various mosques as centers of Islamic activities as practiced Syaikh Hasan Ma’shum (1884-1937) in Medan, Syaikh Ja’far Abdul Qodir Al Mandily (1894-1958) and his younger brother Syaikh Muhammad Ya’kub Abdul Qodir Al Mandily (1914-1984) in Panyabungan, Madina. Then Islamic education developed and  institutionalized  with  the  founding  of  the  establishment  of  the  Musthafawiyah Islamic Boarding  School  in  Purbabaru,  Madina,  Madrasah Maslurah  (1912) and  the Aziziyah Madrasah (1923) in Tanjung pura, Langkat,  Maktab  Islamiyah Tapanuli in Medan (1918) then the establishment  of Islamic colleges and universities. In addition, the  development  of Islamic education  in North  Sumatra  was also driven by several leaders/ scholars such as Syaikh Mustafa Husein, Syaikh Abdul Halim Khatib, Syaikh M. Arsyad Thalib  Lubis and Syaikh Ali Hasan Ahmad Ad-Dary. Syaikh Ali Hasan Ahmad Ad-Dary's contribution in Islamic Education in North Sumatra is writing several Islamic education textbooks as a guide for students in the teaching and learning process, publishing and printing several Islamic education textbooks through his publishers Penerbit   Al-Mahfuzh   Budi,   established   several   Islamic   schools,   madrasas   and universities in North Sumatra. Syaikh Ali Hasan Ahmad Ad-Dary also participated  in establishing the North Sumatra State Islamic Institute (IAIN SU).